Impact of a CD36 inhibitor on Porphyromonas gingivalis mediated atherosclerosis. (June 2021) - Rekhi, Umar Rauf; Catunda, Raisa Queiroz; Alexiou, Maria; Sharma, Monika; Fong, Aaron; Febbraio, Maria
Highlights: CD36 inhibitor, AP5055 abrogates atherosclerotic lesion burden associated with periodontal disease. In vitro analysis showed that AP5055 inhibited the transcriptional activity of NF-κB. AP5055 decreased levels of cholesterol in plasma. AP5055 has a role in the reduction of pro-inflammatory cytokines. Abstract: Objective: To determine if AP5055 drug, an inhibitor of CD36, prevents the increase in Porphyromonas gingivalis (P. gingivalis) mediated atherosclerosis in low-density lipoprotein receptor knockout (LDLR KO) mice by targeting CD36. Methods: Male LDLR KO mice were infected with P. gingivalis by oral lavage to induce periodontal disease and fed a western diet to induce atherosclerosis. Mice were treated with the CD36 inhibitor, AP5055 (1 mg/kg), or vehicle (1% DMSO). Aortae were dissected and stained with oil red-O for morphometric analysis; blood/plasma was collected to determine markers of inflammation by cytokine array and cholesterol levels. P. gingivalis -induced bone loss in mandibles was assessed using micro-CT. P. gingivalis lipopolysaccharide stimulated nuclear factor-kappa B (NF-κB) activity was measured using a reporter gene (secreted alkaline phosphatase) assay in AP5055 treated or untreated RAW-Blue macrophages. Results: Isolated aortae showed a significant decrease in lesion area in the AP5055 treated group as compared to the control group. Mechanistically, in vitro analysis demonstrated that AP5055 inhibited NF-κB activity. Cytokine array showed a decrease in the expression of pro-inflammatory cytokines and decreased levels of plasma cholesterol in AP5055 treated mice. Micro-CT measurements of bone loss were not significant between the two groups. Conclusion: CD36 inhibitor AP5055 abrogates atherosclerotic lesion burden associated with periodontal disease, accompanied by a reduction in markers of inflammation. These experiments may support the development of drugs targeting CD36 for human disease.